Embutido cárneo tipo salaminho: adição de probiótico e substituição parcial da gordura por inulina - Araújo, Antonia Daiana Andrade (2018)
The use of probiotics is promising in fermented raw sausage because they do not require heating. The addition of Lactobacillus paracasei (probiotic) to salami and the replacement of backfat by inulin (prebiotic) may reduce the health risks associated with the consumption of meat sausage, such as obesity and intestinal disorders. The objective of this study was to optimize and characterize a salami-type meat-sausage formulation added with probiotic and partially replace the backfat by inulin fiber. A rotational central composite (DCCR) 22 design with 4 axial and 3 central points was used, having as independent variables the backfat and inulin and variables responses the reduction of lipid content and number of viable cells of Lactobacillus paracasei. A comparative study of the symbiotic (optimized) formulation and a control formulation of salami-type meat sausage was carried out, as well as the evolution of pH, water activity, weight loss and lactic acidity during the fermentation stage. At the end of the processing, the functional quality was evaluated through the viability analysis of Lactobacillus paracasei, its gastrointestinal resistance in vitro and determination of total fiber content. During storage, the physicochemical and microbiological properties of the formulations were compared. The symbiotic formulation was evaluated for the acceptance of its sensory attributes and purchase intention. The optimization resulted in a symbiotic formulation with 4% inulin and 5% of backfat, with a lipid reduction of 37%, viability of Lactobacillus paracasei higher than 6 log (UFC / g) in both, the alimentary matrix and the in vitro gastrointestinal test. The symbiotic formulation was superior to the control formulation regarding the physical, physicalchemical and microbiological parameters. The sensorial attributes of the symbiotic formulation were acceptable and the purchase intention was 61%. Thus, it is possible to use inulin as a partial substitute for backfat in the sausage-type meat sausage formulation, added with Lactobacillus paracasei, providing lipid reduction without altering its physicochemical, microbiological, sensorial and potentially probiotic characteristics.